THE IMPACT OF USING THE SPIN WELL EDUCATIONAL TOOL ON DEVELOPING ARABIC LANGUAGE SKILLS - Muh Abrar; Lukman Taufik Akasahtia; Asriani Asriani; Ismail Abdullah Hussein (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2026)
Arabic language learning at the elementary madrasah level often faces challenges, particularly the low activeness and memory retention of students in understanding new vocabulary. This study aims to determine the effect of using the Spinn Well media on the activeness and memory of second-grade students at MI Mismathla’ul Anwar in the Adawatul Madrosiyah material. The research employed a descriptive qualitative method through observation, interviews, and documentation of 30 students. The results show that the implementation of the Spinn Well media combined with the mubasyaroh method successfully increased students’ active participation in reading, writing, and memorizing Arabic vocabulary. In addition, this media also helped students retain the material more easily since learning was delivered in an enjoyable and interactive way. In conclusion, the use of Spinn Well is effective in creating a lively learning atmosphere, motivating students, and improving their language skills.